Peningkatan Kapasitas Kader melalui Program Royco Nutrimenu-Edufamily: Mendukung Pencegahan Stunting di Kota Bogor - Tin Herawati; Dodik Briawan; Yulina Eva Riany; Ikeu Ekayanti (Institut Pertanian Bogor, 2025)
Indonesia still faces various challenges that hinder the development of high-quality human resources in the future, one of which is nutrition and health. Stunting is an unresolved nutritional problem. This study aimed to improve cadres’ knowledge and skills as a step toward preventing stunting. This study used a pre-post intervention design to analyze changes in cadres’ knowledge, attitudes, and skills after participating in the Royco Nutrimenu-Edufamily training program. The methods used included socialization and training on stunting, complementary feeding (MPASI), and counseling skills. The data were collected using an online questionnaire. The activity was carried out in July 2023, involving 100 cadres from 10 villages in Bogor City: Situ Gede, Bubulak, Margajaya, Balumbang Jaya, Sindang Barang, Gunung Batu, Loji, Curug, Pasir Kuda, and Semplak. The materials covered were 1) The dangers and prevention of stunting; 2) The importance of MPASI for child growth and development; 3) The Royco Nutrimenu MPASI program; and 4) Tips on becoming a counselor. After training, each cadre provided education and MPASI cooking demonstrations to mothers with children aged 6‒24 months. Each cadre educated 10 mothers, for a total of 1000 mothers. The results showed an increase in cadres’ knowledge and skills after the training. In addition, cadres were able to transfer the knowledge and skills they acquired.